Design and evaluation of a low‑cost real‑time fluid-level monitoring system for fuel stations - Jovianne Birindwa; Stéphane Birindwa Birhashwirwa (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
Accurate fluid level management in fuel stations is hampered by inventory errors, delayed shortage detection and costly proprietary sensors. We designed and built a low‑cost, open‑source monitoring system using an Arduino Uno, an HC‑SR04 ultrasonic sensor, a NodeMCU ESP8266 and a DHT11 temperature sensor. Validation was restricted to static short-term conditions, with a prototype tested in a 200 cm tank over 62 hours and 32 paired measurements collected at two-hour intervals. Prototype readings were compared with dipstick measurements after temperature compensation. The system achieved a mean error of 0.03 cm, a mean absolute error of 0.91 cm, a standard deviation of 1.06 cm and a root‑mean‑square error of 1.05 cm, with a 95 % confidence interval of ±0.37 cm. These results demonstrate that a calibrated and temperature‑compensated ultrasonic sensor can deliver centimetre‑level accuracy suitable for inventory management in resource‑constrained fuel stations. Future work will extend validation to dynamic transfers, sloshing/vibration, humidity effects, and long-term drift in operational tanks.